Characterization of the Self-Healing Mechanism of VHB 4910. (2016) - Fan, Fan; Szpunar, Jerzy
Abstract: Self-healing materials have been heavily studied because of its ability to extend the service life of materials. However, current self-healing materials with strong mechanical property requires energy input to trigger the healing process while the materials with autonomous self-healing ability are not tough enough for practical applications. Surprisingly, we found a commercial material, VHB 4910, compromising a strong mechanical property as elastomers and rapid self-healing ability as hydrogels. We confirmed the self-healing ability of VHB 4910 with tensile tests. Raman and infrared spectra illustrate the bonding structure of this material. X-ray diffraction pattern shows an amorphous inner structure of this material. We confirmed that both hydrogen bonding and chain diffusion process contributed to the self-healing ability.